Protein-protein interactions in the rigor actomyosin complex. - Milligan, R A (1996)
Since it has not been possible to crystallize the actomyosin complex, the x-ray structures of the individual proteins together with data obtained by fiber diffraction and electron microscopy have been used to build detailed models of filamentous actin (f-actin) and the actomyosin rigor complex. In the f-actin model, a single monomer uses 10 surface loops and two alpha-helices to make sometimes complicated interactions with its four neighbors. In the myosin molecule, both the essential and regulatory light chains show considerable structural homology to calmodulin. General principles are evident in their mode of attachment to the target alpha-helix of the myosin heavy chain. The essential light chain also makes contacts with other parts of the heavy chain and with the regulatory light chain. The actomyosin rigor interface is extensive, involving interaction of a single myosin head with regions on two adjacent actin monomers. A number of hydrophobic residues on the apposing faces of actin and myosin contribute to the main binding site. This site is flanked on three sides by charged myosin surface loops that form predominantly ionic interactions with adjacent regions of actin. Hydrogen bonding is likely to play a significant role in actin-actin and actin-myosin interactions since many of the contacts involve loops. The model building approach used with actomyosin is applicable to other multicomponent assemblies of biological interest and is a powerful method for revealing molecular interactions and providing insights into the mode of action of the assemblies.